Kemampuan Membaca Kitab Kuning Mahasiswa Perguruan Tinggi Islam Berbasis Pesantren - Abdurrahman, Abdurrahman; Dhiauddin, Dhiauddin; Assegaf, S. Syech (YASIN, 2025)
This study examines the basic competencies of Arabic grammar among students at two Islamic universities based in Islamic boarding schools, Al-Qolam University in Malang and the Islamic University of Aceh, and their influence on the ability to read the yellow book (Kitab Kuning). The majority of students have proven to have good basic competencies, including understanding nahwu, shorof, and vocabulary. These competencies are positively correlated with the ability to read the yellow book, which is generally acquired from Islamic boarding schools, although some also acquire it from other sources. The objectives of this study are to (1) identify the basic competencies of Arabic grammar among students, and the sources of acquisition of these competencies, and (2) analyze the level of ability to read the yellow book. A descriptive quantitative method was used with a questionnaire as an instrument. The results of the study show that the majority of students at both universities have fairly good basic competencies in Arabic grammar. These competencies include understanding the structure of sentences (nahwu), the structure and changes of words (shorof), as well as mastering adequate vocabulary. The majority of students who have good Arabic grammar competence are able to read the yellow book fluently. The source of acquisition of the ability to read the yellow book is mostly from Islamic boarding schools, but some are also obtained from outside of Islamic boarding schools. The majority of them make it a learning reference. This study recommends strengthening the learning of Arabic grammar in universities to improve the ability to read the yellow book.